Magnetism and multiferroicity of an isosceles triangular lattice antiferromagnet Sr3NiNb2O9. (23rd September 2016) - Lee, M; Choi, E S; Ma, J; Sinclair, R; Dela Cruz, C R; Zhou, H D
Abstract: Various experimental measurements were performed to complete the phase diagram of a weakly distorted triangular lattice system, Sr3 NiNb2 O9 with Ni 2+ , spin-1 magnetic ions. This compound possesses an isosceles triangular lattice with two shorter bonds and one longer bond. It shows a two-step magnetic phase transition at T N 1 ∼ 5.1 K and T N 2 ∼ 5.5 K at zero magnetic field, characteristic of an easy-axis anisotropy. In the magnetization curves, a series of magnetic phase transitions was observed such as an up-up-down phase at μ 0 H c 1 ∼ 10.5 T with 1/3 of the saturation magnetization ( M sat ) and an oblique phase at μ 0 H c 2 ∼ 16 T with 3 /3 M sat . Intriguingly, the magnetic phase transition below T N2 is in tandem with the ferroelectricity, which demonstrates multiferroic behaviors. Moreover, the multiferroic phase persists in all magnetically ordered phases regardless of the spin structure. The comparison between the phase diagrams of Sr3 NiNb2 O9 and its sister compound with an equilateral triangular lattice antiferromagnet Ba3 NiNb2 O9 (Hwang et al 2012 Phys. Rev. Lett .109 257205), illustrates how a small imbalance among exchange interactions change the magnetic ground states of the TLAFs.